Exploring the Efficacy of Pre-Marital Counseling Programmes in Reducing Divorce Rates - Elegbede, Christie Bola (Researchparks Publishing, 2026)
This study examines the effectiveness of pre-marital counselling interventions on decreasing divorce, specifically the effects on relationship satisfaction, communication competence, and conflict resolution between couples who are engaged. The aims of this study are to evaluate the impact of pre-marital counselling on marital satisfaction among couples prior and subsequent to marriage, to explore the impact of different methods of counselling in improving communication skills, and to identify the relationship between attending pre-marital counselling and whether or not the couples will attend additional assistance in case of marital problems. Furthermore, the study explores how pre-marital counselling can repair and manage the issues of conflict areas the couples have identified. With comparative approach, we analyze divorce differences among couples who receive pre-marital counselling and those who do not receive counselling and discover particular counselling factors that make an important contribution to enduring marriages in the context of long-term duration. With proper literature review method, this study formulates better understanding of pre-marital counselling advantages. Early indications are that pre-marital programs help in building effective communication, enhance the quality of satisfaction within the relationship, and significantly reduce levels of divorce. The study emphasizes the necessity of foresight, e.g., pre-marital therapy, in creating healthy, long-term marriages.